A large-cohort retrospective study of metastatic patterns and prognostic outcomes between inflammatory and non-inflammatory breast cancer. (June 2020) - Wang, Zheng; Wang, Hui; Ding, Xinyuan; Chen, Xiaosong; Shen, Kunwei
Background and aims: Breast cancer-related death is attributable mainly to metastasis. Inflammatory breast cancer (IBC) is an infrequent subtype of breast cancer that shows a relatively high rate of metastasis. In this study, we aimed to compare the metastatic patterns and prognostic outcomes of IBC and non-inflammatory breast cancer (non-IBC). Methods: We extracted data between 2010 and 2014 from the Surveillance, Epidemiology and End Results (SEER) database. The Chi-square test and Fisher's exact test were used to compare the categorical parameters among different groups. Logistic regression was applied for multivariate analysis. The Kaplan–Meier method and multivariate Cox regression models were performed to analyze prognosis. Results: We enrolled 233, 686 breast cancer patients between 2010 and 2014 in our research, including 2806 IBC and 230, 880 non-IBC patients. Compared with the non-IBC group, the IBC group tended to have a higher incidence of the human epidermal growth factor receptor 2 positive (HER2+) and triple-negative breast cancer (TNBC) subtypes, older age, a higher rate of unmarried status, a lower incidence of black race, poorer tumor differentiation, larger tumor sizes, and a higher frequency of regional lymph node invasion. IBC and non-IBC shared similar trends in molecular subtypes among different metastatic organs. The percentage of the hormone receptor positive (HR+)/human epidermal growth factor receptor 2 negative (HER2–) subtype decreased gradually in patients with lung (IBC 42.5%, non-IBC 55.7%), distant lymph node (IBC 41.5%, non-IBC 54.6%), liver (IBC 31.1%, non-IBC 46.7%), and brain (IBC 30.6%, non-IBC 47.9%) metastases compared with that in patients with bone (IBC 50.8%, non-IBC 69.0%) metastasis in both cohorts. In both the IBC and non-IBC cases, the proportion of visceral metastases increased in the TNBC subtype, especially brain metastasis (IBC 26.4%, non-IBC 21.2%), which had the largest increase. The frequencies of all sites (bone, lung, liver, brain, and distant lymph node) in IBC were much higher than those in non-IBC (bone: IBC 21.1%, non-IBC 3.0%; lung: IBC 11.4%, non-IBC 1.4%; liver: IBC 9.6%, non-IBC 1.2%; brain: IBC 2.6%, non-IBC 0.3%; distant lymph node: IBC 12.9%, non-IBC 1.0%). The most frequent bi-site metastasis was the bone and liver (IBC 2.5%, non-IBC 0.3%), and the most frequent tri-site combination was the bone, lung, and liver (IBC 1.1%, non-IBC 0.2%). Kaplan–Meier curves and multivariate Cox regression models suggested that the IBC cohort had poorer overall survival [hazard ratio (HR) 1.602, 95% confidence interval (CI) 1.496–1.716, p  < 0.001] and breast cancer-specific survival (HR 1.511, 95% CI 1.402–1.628, p  < 0.001) than the non-IBC cohort. Furthermore, univariate and multivariate analyses indicated that IBC was an independent prognostic factor in patients with different metastatic sites. Conclusion: IBC and non-IBC patients presented with different metastatic frequencies, clinical features and prognostic outcomes. Our findings provide more information for therapeutic decision making and clinical study designs.